Alcohol-induced damage to the fimbria/fornix reduces hippocampal-prefrontal cortex connection during early abstinence - Pérez-Cervera, Laura; De Santis, Silvia; Marcos, Encarni; Ghorbanzad-Ghaziany, Zahra; Trouvé-Carpena, Alejandro; Selim, Mohamed Kotb; Pérez-Ramírez, Úrsula; Pfarr, Simone; Bach, Patrick; Halli, Patrick; Kiefer, Falk; Moratal, David; et al. (Acta Neuropathologica Communications, 2023)
Alcohol dependence is characterized by a gradual reduction in cognitive control and inflexibility to contingency changes. The neuroadaptations underlying this aberrant behavior are poorly understood. Using an animal model of alcohol use disorders (AUD) and complementing diffusion-weighted (dw)-MRI with quantitative immunohistochemistry and electrophysiological recordings, we provide causal evidence that chronic intermittent alcohol exposure affects the microstructural integrity of the fimbria/fornix, decreasing myelin basic protein content, and reducing the effective communication from the hippocampus (HC) to the prefrontal cortex (PFC). Using a simple quantitative neural network model, we show how disturbed HC-PFC communication may impede the extinction of maladaptive memories, decreasing flexibility. Finally, combining dw-MRI and psychometric data in AUD patients, we discovered an association between the magnitude of microstructural alteration in the fimbria/fornix and the reduction in cognitive flexibility. Overall, these findings highlight the vulnerability of the fimbria/fornix microstructure in AUD and its potential contribution to alcohol pathophysiology.
Veröffentlicht: 21. Juni 2023
Gesehen am 14.08.2023